Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Nilai Perusahaan - Rachman Indriyanto, Ridho Aulia; Syaiful, Syaiful (Universitas Muhammadiyah Gresik, 2024)
This research aims to determine the effect of company size, leverage and profitability on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. This research uses quantitative methods and uses secondary data as the data source. The sampling technique used purposive sampling technique by obtaining a sample of 19 companies. This test uses multiple linear regression. The regression results show that company size influences company value. Leverage has no effect on company value. Profitability has no effect on company value.